Management and prevention of refeeding syndrome in medical inpatients: An evidence-based and consensus-supported algorithm - Friedli, Natalie; Stanga, Zeno; Culkin, Alison; Crook, Martin; Laviano, Alessandro; Sobotka, Lubos; Kressig, Reto W; Kondrup, Jens; Mueller, Beat; Schuetz, Philipp (Nutrition, 2018)
OBJECTIVES: Refeeding syndrome (RFS) can be a life-threatening metabolic condition after nutritional replenishment if not recognized early and treated adequately. There is a lack of evidence-based treatment and monitoring algorithm for daily clinical practice. The aim of the study was to propose an expert consensus guideline for RFS for the medical inpatient (not including anorexic patients) regarding risk factors, diagnostic criteria, and preventive and therapeutic measures based on a previous systematic literature search. METHODS: Based on a recent qualitative systematic review on the topic, we developed clinically relevant recommendations as well as a treatment and monitoring algorithm for the clinical management of inpatients regarding RFS. With international experts, these recommendations were discussed and agreement with the recommendation was rated. RESULTS: Upon hospital admission, we recommend the use of specific screening criteria (i.e., low body mass index, large unintentional weight loss, little or no nutritional intake, history of alcohol or drug abuse) for risk assessment regarding the occurrence of RFS. According to the patient's individual risk for RFS, a careful start of nutritional therapy with a stepwise increase in energy and fluids goals and supplementation of electrolyte and vitamins, as well as close clinical monitoring, is recommended. We also propose criteria for the diagnosis of imminent and manifest RFS with practical treatment recommendations with adoption of the nutritional therapy. CONCLUSION: Based on the available evidence, we developed a practical algorithm for risk assessment, treatment, and monitoring of RFS in medical inpatients. In daily routine clinical care, this may help to optimize and standardize the management of this vulnerable patient population. We encourage future quality studies to further refine these recommendations.
Keywords: lékařská praxe založená na důkazech; Nutrition Assessment; hodnocení rizik; lidé; Inpatients; Evidence-Based Practice; konsensus; Risk Assessment; Algorithms; Refeeding Syndrome; plošný screening; Decision Support Techniques; Consensus; Risk Factors; směrnice pro lékařskou praxi jako téma; Practice Guidelines as Topic; rizikové faktory; algoritmy; Mass Screening; hodnocení stavu výživy; metody pro podporu rozhodování; realimentační syndrom; hospitalizovaní pacienti; Humans